Thrips of the suborder Terebrantia (Insecta: Thysanoptera) from the Bogotá plateau - CALIXTO-ÁLVAREZ, CLAUDIA LILIANA (Revista Colombiana de Entomología, 2005)
An inventory was conducted of the species pertaining to the suborder Terebrantia present in the Bogotá plateau. The insects were collected in the field and taken to the laboratory for identification to species. A list was made of the species found in the Bogotá plateau, including new records for Colombia, new altitude records, and some biological observations. New records of plant associations with different thrips species are also mentioned. Seventy-nine species distributed in 23 genera and three families were identified for the Bogotá plateau; of these, 43% are new records for Colombia.